A Capacitorless and Low‐Optical‐Flicker AC Direct LED Driving IC and System Applied to Street Lighting. Issue 7 (11th May 2021) - Sun, Longtian; Han, Yan
Abstract : This study presents a novel alternating current (AC) direct light emitting diode (LED) driving integrated circuit (IC) and system applied to street lighting. In the proposed driving IC, the level shifter circuit is specially designed to enable it to be directly powered by the 380 V 50 Hz three‐phase AC, so that the characteristics of the three‐phase AC can be utilized to reduce the harmful optical flicker and increase the output power of the driving system. And a new power factor correction circuit is proposed to improve the power factor of the driving IC. In addition, the power compensation circuit with negative feedback is designed to stabilize the average output power when the voltage of the power grid fluctuates. The driving IC and system are fabricated with a 1 μm 700 V Bipolar‐CMOS‐DMOS process. The driving system does not need electrolytic capacitors, achieves 72 W output power and an up to 0.993 PF with only 12.7% percent flicker at the 380 V 50 Hz three‐phase AC input, while the frequency of the output power is improved to 300 Hz, and the average output power varies only from −2.3% to 0.7% with the help of the power compensation circuit. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.